The trapezius myocutaneous flap for reconstruction of latreral skull base defects - Raja Lope Ahmad, Raja Ahmad Al'konee; Wan Leman, Wan Ishlah; Kamarudin, Norie Azilah (2005)
Extensive tumor involving temporal bone may pose a difficult problem in reconstructive standpoint. These tumors are typically aggressive as well as locally advanced which require wide resections combined with parotidectomy and / or neck dissection resulting in extensive soft tissue and skin defects. The principles in reconstruction of lateral skull base defects are to maintain the symmetry, cosmesis of the lateral skull structures, to achieve dead-space obliteration and finally to bave a quality vascularized tissue which able to withstand adjuvant radiotherapy treatment. We present our early experience in managing two patients with different type of lateral skull base tumor undergoing extensive resection of lateral skull base. The local defects were reconstructed with two different type of pedicled trapezius myocutaneous flap . The techniques used in reconstruction of the defects are addressed.